Pharmacokinetics and tolerance of desciclovir, a prodrug of acyclovir, in healthy human volunteers. - Petty, B G (1987)
Because of the incomplete absorption of acyclovir (ACV) when given orally in humans, efforts have been made to develop a prodrug of ACV that would be better absorbed from the gastrointestinal tract and then converted in vivo to ACV. One such compound, desciclovir (DCV), is converted to acyclovir in vivo by xanthine oxidase. We gave each of 13 healthy volunteers 250 mg (about 3.25 mg/kg of body weight) of DCV orally thrice daily for 10 days, collected serial plasma and urine specimens, and measured DCV and ACV concentrations. The absorption of DCV was at least 75%, and almost two-thirds of the administered oral dose was recovered in the urine as ACV. Peak ACV levels in plasma were about 5 micrograms/ml and were reached in less than 1 h. The levels of ACV achieved in plasma were of the same magnitude as those reported for subjects given intravenous ACV at a dose of 2.5 mg/kg and approximately 10-fold higher than levels attained after administration of 200 mg of oral ACV every 4 h as measured in previous studies. The half-life of DCV was 0.85 +/- 0.16 h, compared with 2.6 +/- 0.5 h for ACV, indicating rapid conversion of DCV to ACV. There was no substantial increase in ACV levels in plasma on day 11 compared with day 2. No serious or consistent adverse effects were noted. In particular, the creatinine level in serum did not significantly rise in any subject and remained within the normal range in all.